Dietary practices and FODMAPs in South Asia: Applicability of the low FODMAP diet to patients with irritable bowel syndrome. Issue 2 (26th January 2018) - Hewawasam, Samapriya P; Iacovou, Marina; Muir, Jane G; Gibson, Peter R
Abstract: The low Fermentable Oligosaccharides, Disaccharides, and Monosaccharides And Polyols (FODMAP) diet has been described, evaluated, and found efficacious for the treatment of patients with irritable bowel syndrome primarily in Western countries. The aim of this review was to address the applicability of this diet to South Asia. The high prevalence of irritable bowel syndrome in South Asia and its associated effects of quality of life and economics warrant the introduction of efficacious therapies. The considerable heterogeneity of dietary patterns and methods of food preparation across South Asian countries and a paucity of food analysis limit precision in defining foods that are high or low in FODMAPs. Spices and condiments are commonly consumed and mostly have a low FODMAP content. However, major high FODMAP sources are frequently used and include onion, garlic, shallots, legumes/pulses, and wheat‐based products, as well as coconut and milk products, offering an opportunity for dietary management to reduce the symptom load. The feasibility of instituting a restrictive diet in which foods with a high FODMAP content are replaced by foods low in FODMAPs must be addressed as a substantial proportion of the nutritional intake including energy, proteins, and micronutrients, is often obtained from FODMAP‐rich food. Furthermore, limited knowledge of health professionals together with a paucity of dietitians further challenge the practicality of introducing the diet. Thus, while the use of the low FODMAP diet in South Asia may be more limited than in westernized countries, it does offer potential therapeutic opportunities, the efficacy, and impact of which require further investigation.